An Anaplastic Lymphoma Kinase-positive Inflammatory Myofibroblastic Tumor with Rapidly Acquired Resistance to First-line Anaplastic Lymphoma Kinase Inhibitor: A Case and Literature Review - Shu-Cheng Wu; Hsing-Wu Chen (Journal of Cancer Research and Practice)
Inflammatory myofibroblastic tumors (IMTs) are soft-tissue neoplasms with rare metastatic potential. Approximately half of IMTs are positive for an anaplastic lymphoma kinase (ALK) gene rearrangement which causes aberrant expression. Early phase clinical trials have demonstrated the efficacy of ALK inhibitors in the treatment of IMTs. However, there is no definite conclusion on which ALK inhibitor performs best, and data regarding subsequent therapy after first-line ALK inhibitor failure are scarce. Here, we report a case of ALK+ metastatic IMT that demonstrated a dramatic response to first-line alectinib but resulted in rapidly acquired resistance. Repeated biopsy and next-generation sequencing (NGS) showed ALK:c.3604G>A; p.(Gly1202Arg), which is a common mechanism of drug resistance in ALK fusion-positive non-small cell lung cancer. We also report subsequent treatment choices and responses in this patient and perform a literature review regarding similar cases as this rare tumor.